La Palingénésie philosophique de Charles Bonnet : le pouvoir heuristique d’un imaginaire matérialiste des Lumières - Sukiennicka, Marta (Studia Romanica Posnaniensia, 2018)
The works of Charles Bonnet illustrate the contribution of imagination to research in natural history in the second half of the 18th century. In his Palingénésie philosophique (1769), Bonnet uses images and metaphors rooted in the philosophical and literary imagery of the Enlightenment to describe the evolution of life. This juxtaposition of scientific and literary discourses did not prevent Bonnet from being regarded as a forefather of modern biology by historians of science.